Corporate governance and firm profitability: evidence from Korea before the economic crisis - Joh, Sung Wook (Journal of Financial Economics, 2003)
This study examines how ownership structure and conflicts of interest among shareholders under a poor corporate governance system affected firm performance before the crisis. Using 5,829 Korean firms subject to outside auditing during 1993–1997, the paper finds that firms with low ownership concentration show low firm profitability, controlling for firm and industry characteristics. Controlling shareholders expropriated firm resources even when their ownership concentration was small. Firms with a high disparity between control rights and ownership rights showed low profitability. When a business group transferred resources from a subsidiary to another, they were often wasted, suggesting that “tunneling” occurred. In addition, the negative effects of control-ownership disparity and internal capital market inefficiency were stronger in publicly traded firms than in privately held ones.